2004
DOI: 10.1523/jneurosci.1301-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Juvenile Myoclonic Epilepsy GABAAReceptor α1 Subunit Mutation A322D Produces Asymmetrical, Subunit Position-Dependent Reduction of Heterozygous Receptor Currents and α1 Subunit Protein Expression

Abstract: Individuals with autosomal dominant juvenile myoclonic epilepsy are heterozygous for a GABA A receptor ␣1 subunit mutation (␣1A322D). GABA A receptor ␣␤␥ subunits are arranged around the pore in a ␤-␣-␤-␣-␥ sequence (counterclockwise from the synaptic cleft). Therefore, each ␣1 subunit has different adjacent subunits, and heterozygous expression of ␣1(A322D), ␤, and ␥ subunits could produce receptors with four different subunit arrangements:Expression of a 1:1 mixture of wild-type and ␣1(A322D) subunits with ␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 46 publications
4
29
0
2
Order By: Relevance
“…immunoblots of cellular lysates containing rat ␣1␤2␥2 or ␣1(A322D)␤2␥2 receptors stained with a polyclonal anti-rat ␣1 antibody (7). Previously, using quantitative fluorescence spectroscopy, we showed that the A322D mutation reduced ␣1(A322D)-GFP subunit fluorescence (10), and, using immunoblots with a monoclonal antibody, we showed that A322D reduced total cellular ␣1(A322D) subunit expression (9,10). Immunoblot experiments depicted in Fig.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…immunoblots of cellular lysates containing rat ␣1␤2␥2 or ␣1(A322D)␤2␥2 receptors stained with a polyclonal anti-rat ␣1 antibody (7). Previously, using quantitative fluorescence spectroscopy, we showed that the A322D mutation reduced ␣1(A322D)-GFP subunit fluorescence (10), and, using immunoblots with a monoclonal antibody, we showed that A322D reduced total cellular ␣1(A322D) subunit expression (9,10). Immunoblot experiments depicted in Fig.…”
Section: Discussionmentioning
confidence: 76%
“…The effect of the A322D mutation on total cellular ␣1 subunit expression is disputed. Immunoblots of lysates from cells transfected with rat ␣1␤2␥2 or ␣1(A322D)␤2␥2 receptors probed with a polyclonal anti-rat ␣1 subunit antibody did not differ by visual inspection (7), but immunoblots from cells transfected with human ␣1␤2␥2 and ␣1(A322D)␤2␥2 subunits and stained with a monoclonal antihuman ␣1 subunit antibody demonstrated that ␣1(A322D) subunit expression was reduced (9). To address this discrepancy, we transfected cells with cDNAs encoding rat ␣1␤2␥2, ␣1(A322D)␤2␥2, ␣1-FLAG␤2␥2, or ␣1(A322D)-FLAG␤2␥2 subunits and performed immunoblots with the same polyclonal ant-rat ␣1 antibody used by the investigators who found no difference in ␣1 and ␣1(A322D) expression (7) (Fig.…”
Section: A322dmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Raol et al (2006b) showed that an increased level of GABA A R α 1 subunits in the dentate gyrus can affect the development of spontaneous seizures after status epilepticus. In addition, recent studies have identified the α 1 (A294D) and α 1 (A322D) genetic mutations of the GABA A R α 1 subunit that are associated with juvenile myoclonic epilepsy (Cossette et al, 2002;Gallagher et al, 2004;Mizielinska et al, 2006). These mutations affect GABA A R gating, expression, and/or trafficking of the receptor to the cell surface -all pathophysiological mechanisms that result in neuronal disinhibition, cause hyperexcitability throughout the brain, and predispose to epileptic seizures (Fisher, 2004;Krampfl et al, 2005;Macdonald et al, 2006).…”
Section: Discussionmentioning
confidence: 99%